One-year randomized controlled trial with different physical-activity programs to reduce musculoskeletal symptoms in the neck and shoulders among office workers - Blangsted, Anne Katrine; Søgaard, Karen; Hansen, Ernst A.; Hannerz, Harald; Sjøgaard, Gisela (Scandinavian Journal of Work, Environment & Health, 2008)
' ' OBJECTIVES ': 'This study evaluates the effect of two different worksite physical-activity interventions on neck–shoulder symptoms, together with perceived work ability and sick leave among office workers. ' ' METHODS ': 'An examiner-blinded randomized controlled trial was conducted with 549 office workers allocated to one of three intervention groups: one with specific resistance training (SRT) of the neck–shoulder region (N=180), one with all-round physical exercise (APE) (N=187), and one which acted as a reference group, which was informed about general health-promoting activities but did not include a physical activity program (N=182). Questionnaires were filled out at baseline and after 1 year of training. ' ' RESULTS ': 'The duration and intensity of neck and shoulder symptoms was lower after the specified worksite physical-activity interventions than in the reference group. On an intervention group level, SRT was not more effective than APE in reducing the duration and intensity of neck and shoulder symptoms. However, those asymptomatic at baseline had a significant lower prevalence of neck–shoulder symptoms at follow-up when allocated to the SRT group than placed in the APE group or reference group. At baseline the work ability index (WAI) was close to 90% of the maximum score, and the mean sick leave was 5 days per year, both being unaffected by the interventions. ' ' CONCLUSIONS ': 'Different physical-activity interventions were successful in reducing neck–shoulder symptoms, and SRT was superior to APE in the primary prevention of such symptoms. The initially relatively high WAI was the most probable reason for no further increase in WAI. Likewise the mean sick leave the year before the intervention was very low, and it was probably not possible to reduce it further.
Keywords: musculoskeletal symptom; neck; office worker; physical training; physical-activity program; randomized controlled trial; resistance training; shoulder; sick leave; work ability; worksite